Assessment of Groundwater Pollution and its Impact in and around Punnam Area of Karur District, Tamilnadu, India - G. Raja; P. Venkatesan (E-Journal of Chemistry)
Various samples of groundwater were collected from different areas in and around the Punnam village of Karur District, India and analyzed for their physicochemical characteristics. The results of this analysis were compared with the water quality standards of WHO and CPHEEO. In this analysis the various physicochemical parameters such as pH, electrical conductivity, turbidity, total dissolved solids, Cl-, F-, SO42-, NO3-, Na+, K+, Fe, Cr, calcium and magnesium etc., were determined using standard procedures. The quality of groundwater samples were discussed with respect to these parameters and thus an attempt were made to ascertain the quality of groundwater used for drinking and cooking purposes in the sampling areas.